Efficacy and safety of combined immunotherapy and antiangiogenesis with or without chemotherapy for advanced non-small-cell lung cancer: A systematic review and pooled analysis from 23 prospective studies - Gao, Ruo-Lin; Song, Jun; Sun, Li; Wu, Zhi-Xuan; Yi, Xiao-Fang; Zhang, Shu-Ling; Huang, Le-Tian; Ma, Jie-Tao; Han, Cheng-Bo (Frontiers in Pharmacology, 2022)
Purpose: Immune checkpoint and antiangiogenic inhibitors have a potentially synergistic antitumor effect. We aimed to assess the efficacy and safety of immunotherapy in combination with antiangiogenesis therapy with or without chemotherapy in patients with advanced non-small-cell lung cancer (NSCLC). Methods: PubMed, Embase, the Cochrane library, Google Scholar, Ovid, Scopus, and Web of Science were searched for eligible trials. ClinicalTrials.gov and meeting abstracts were also searched for qualified clinical studies. The inclusion criteria were as follows: prospective studies (including single-arm studies) that evaluated efficacy and/or toxicity of immunotherapy combined with antiangiogenic agents (A+I) with or without chemotherapy (A+I+chemo) in patients with advanced or metastatic NSCLC; and primary outcome of each study reported at least one of these endpoints: progression-free survival (PFS), overall survival, objective response rate (ORR), disease control rate (DCR), or adverse events (AEs). Results: Twenty three prospective studies comprising 1856 patients with advanced NSCLC were included. The pooled ORR, median PFS, and estimated overall survival were 39%, 6.8 months (95% confidence interval [CI], 5.53–8.13), and 18.6 months in the overall group. Similar ORR and median PFS with A+I+chemo versus A+I were observed in patients treated in first-line setting (59% and 9.47 months [95% CI, 6.45–12.49] versus 52% and 10.9 months [95% CI, 1.81–19.98], respectively). We also observed improved ORR and mPFS with A+I+chemo versus A+I in subsequent-line setting (56% and 8.1 months [95% CI, 5.00–11.26] versus 22% and 5.1 months [95% CI, 4.01–6.15], respectively). Efficacy of A+I+chemo therapy was evident across different PD-L1 subgroups, especially in patients with EGFR mutations (ORR: 59%; mPFS: 8.13 months [95% CI: 5.00–11.26]) or baseline liver metastases. The incidence of AEs with a major grade of ≥3 in the overall, A+I, and A+I+chemo groups were 4.1% vs. 5.5% vs. 3.4% for proteinuria, 13.7% vs. 16.2% vs. 9.7% for hypertension, and 1.9% vs. 1.2% vs. 2.8% for rash, respectively. No new safety signals were identified in this pooled analysis.